Pendampingan Usaha sebagai Variabel Moderator pada Pengaruh antara Modal Sendiri dan Jumlah Pembiayaan Murabahah terhadap Omzet - Luthfi, Faishol (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2023)
This study aims to analyze the effect of equity and murabahah financing on MSME turnover with business assistance as a moderating variable. This study uses a mix methods approach which is a combination of quantitative and qualitative methods. The quantitative method uses Moderated Regression Analysis (MRA) and the qualitative method uses descriptive analysis. The independent variables in this research are equity (X1) and the amount of murabahah financing (X2) with business assistance as a moderating variable (Xm). The dependent variable is MSME turnover. The subject of this research is MSME actors in Surabaya City. The sample of this study amounted to 300 people who were taken using purposive sampling method. The results showed that the variable of equity has a positive and significant effect on MSME turnover, while business assistance has been shown to moderate the influence between equity and murabahah financing on MSME turnover. There are several forms of business assistance for MSME actors, namely related to production capacity, business community and product promotion.This study looks at the independent variables from two sides, namely from the internal side of MSME actors, namely their own capital and externally, namely murabahah financing. Further exploration is needed regarding the independent variables in this study.This study is useful for relevant regulators to formulate MSME development policies considering the importance of MSME's role in the Indonesian economy. This study provides deeper insight into business assistance as a moderating variable and also forms of business assistance.